2022
DOI: 10.1177/03000605221117138
|View full text |Cite
|
Sign up to set email alerts
|

CCNB1 and CCNB2 involvement in the pathogenesis of psoriasis: a bioinformatics study

Abstract: Objective The cell cycle-related proteins cyclin B1 (CCNB1) and cyclin B2 (CCNB2) are potentially involved in the underlying mechanisms of psoriasis. The present study aimed to explore this possibility using bioinformatics approaches. Methods CCNB1 and CCNB2 protein levels were evaluated in 14 psoriasis patients and five healthy controls by enzyme-linked immunosorbent assays, and their mRNA levels were evaluated using data from four publicly available datasets (GSE53552, GSE41664, GSE14905, and GSE13355). Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…5,19 The SIRT1/NF-κB signaling pathway is critical in psoriasis regulation. 2 The present study revealed that LARP7 alleviated psoriasis symptoms and promoted its progression in mice.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…5,19 The SIRT1/NF-κB signaling pathway is critical in psoriasis regulation. 2 The present study revealed that LARP7 alleviated psoriasis symptoms and promoted its progression in mice.…”
Section: Discussionsupporting
confidence: 51%
“…1 The exact pathogenesis of psoriasis is still unclear, but it is widely believed that abnormal crosstalk plays an important role in the pathogenesis of psoriasis. 2,3 An extensive network of growth factor circuits, such as epidermal growth factor, vascular endothelial growth factor, and keratinocyte growth factor, as well as cytokines, further mediates keratinocyte cell proliferation. 4 In addition, the critical role of…”
Section: Introductionmentioning
confidence: 99%
“…CCNB1 and CCNB2 may not only regulate the cell cycle of keratinocytes through a variety of pathways, but also regulate immune cells such as macrophages and mast cells, support the release of important signaling molecules, and are involved in and promote the pathogenesis and progression of PS. [33] These results suggest that abnormally high expressions of CDK1 and CCNB1 may lead to changes in the cell cycle process, significantly shortening the cell cycle, promoting the abnormal proliferation of keratinocytes, and participating in the regulation of immune cells such as macrophages and mast cells. It is involved in the pathophysiological process of PS by influencing the biological functions of keratinocytes and immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, CCNB1 and CCNB2 play different roles in mitosis due to their significant differences in subcellular localization. [ 26 , 27 ] In the interphase, CCNB2 is mainly associated with the Golgi apparatus, while CCNB 1 is colocalized with microtubules. In mitotic cells, CCNB 1 binds to chromosomes and is tightly bound to the spindle.…”
Section: Discussionmentioning
confidence: 99%